Two men pulling sled up a snow bank in Skagway Canyon, White Pass Trail, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Handwritten on verso: Skagway Canyon PH Coll 519.U-1 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number